Amino acid restriction, aging, and longevity: an update - Austad, S. N.; Smith, J. R.; Hoffman, J. M. (Frontiers in Aging, 2024)
Abstract. Various so-called dietary restriction paradigms have shown promise for extending health and life. All such paradigms rely on ad libitum (hereafter ad lib) feeding, something virtually never employed in animals whose long-term health we value, either as a control or, except for food restriction itself, for both control and treatment arms of the experiment. Even though the mechanism(s) remain only vaguely understood, compared to ad lib-fed animals a host of dietary manipulations including calorie restriction, low protein, methionine, branched-chain amino acids, and even low isoleucine have demonstrable health benefits in laboratory species in a standard laboratory environment. The remaining challenge is to determine whether these health benefits remain in more realistic environments and how they interact with other health enhancing treatments such as exercise or emerging geroprotective drugs. Here we review the current state of the field of amino acid restriction on longevity of animal models and evaluate its translational potential.